Effectiveness of Sunn Hemp (Crotalaria juncea L.) in Reducing Wireworm Damage in Potatoes - Lorenzo Furlan; Stefano Bona; Roberto Matteo; Luca Lazzeri; Isadora Benvegnù; Nerio Casadei; Elisabetta Caprai; Ilaria Prizio; Bruno Parisi (Insects, 2025)
Wireworms are a major threat to potatoes. Agronomic prevention is always the first IPM strategy to be implemented. This work assesses whether a bioactive cover crop, sunn hemp (Crotalaria juncea L.), a tropical leguminous plant, reduces wireworm damage risk when cultivated as a crop preceding potatoes. The effects of Crotalaria plants (alive, chopped, and incorporated) on wireworms and tuber-damage prevention were studied in semi-natural (pots) and open-field conditions. The survival of a set number of reared wireworms feeding on Crotalaria plants or potato tubers in soil with incorporated Crotalaria chopped tissues was assessed. Wireworm damage on tubers was assessed in fields where Crotalaria had been cultivated, chopped, and incorporated the previous year. The tuber damage assessment involved counting all the erosions/scars caused by wireworm feeding. The prevalent wireworm species studied was Agriotes sordidus. Our research is the first to demonstrate that Crotalaria as a cover crop can significantly reduce potato damage by wireworms. A major role is likely played by the high pyrrolizidine alkaloid content in Crotalaria juncea tissues, but this has to be specifically proven. Crotalaria juncea may thus represent an effective means for use alone or with complementary ones to produce potatoes with low wireworm damage without using synthetic insecticides.